Cryptosporidiosis in ruminants - Ferda Sevinç (Eurasian Journal of Veterinary Sciences)
Cryptosporidium parvum is a primary pathogen in the aetiology of neonalal diarrhea syndrome in ruminants. Cryptosporidiosis is a considerably prevalent disease in many countries, and the disease is ol economic importance especially in calves and goat kids in Turkey. In this review, the diagnosis, treatment, control of cryptosporidiosis in ruminants and its status in Turkey were evaluated.